2023
DOI: 10.1088/1748-605x/acd830
|View full text |Cite
|
Sign up to set email alerts
|

Bioprinted cancer-stromal in-vitro models in a decellularized ECM-based bioink exhibit progressive remodeling and maturation

Abstract: Continuous extracellular matrix (ECM) remodeling and cellular heterogeneity are key contributors to cancer development and can both profoundly affect treatment efficacy. Developing in-vitro models that recapitulate matrix and cellular heterogeneity of the tumor microenvironment (TME) can aid in observations that are currently challenging to acquire with conventional 2D cultures and preclinical animal models. Here we report an extrusion bioprinted co-culture model of head and neck cancer and stromal fibroblasts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 72 publications
0
1
0
Order By: Relevance
“…This capability is pivotal for generating in vitro models that accurately mimic the intricate features of native tissues, facilitating regenerative medical endeavors ( Nam et al, 2015 ; Langhans, 2018 ; Bédard et al, 2020 ; Hwang et al, 2021 ). Recent examples have highlighted the potential of 3D bioprinting in creating in vitro models of human tissues and diseases, including notable applications such as: accurate modeling of the complex tumor microenvironments ( Kort-Mascort et al, 2023 ; Mu et al, 2023 ; Zhou et al, 2023 ); physiologically relevant models for the entire respiratory tract ( Moura et al, 2023 ); replication of native skin features for wound healing studies ( Norahan et al, 2023 ); engineered cardiac tissues such as in vitro cardiac models and vascular channels ( Lu et al, 2023 ); or normal and disease hepatic tissue models ( Sun et al, 2023 ).…”
Section: Elrs For 3d In Vitro Models In Regenerati...mentioning
confidence: 99%
“…This capability is pivotal for generating in vitro models that accurately mimic the intricate features of native tissues, facilitating regenerative medical endeavors ( Nam et al, 2015 ; Langhans, 2018 ; Bédard et al, 2020 ; Hwang et al, 2021 ). Recent examples have highlighted the potential of 3D bioprinting in creating in vitro models of human tissues and diseases, including notable applications such as: accurate modeling of the complex tumor microenvironments ( Kort-Mascort et al, 2023 ; Mu et al, 2023 ; Zhou et al, 2023 ); physiologically relevant models for the entire respiratory tract ( Moura et al, 2023 ); replication of native skin features for wound healing studies ( Norahan et al, 2023 ); engineered cardiac tissues such as in vitro cardiac models and vascular channels ( Lu et al, 2023 ); or normal and disease hepatic tissue models ( Sun et al, 2023 ).…”
Section: Elrs For 3d In Vitro Models In Regenerati...mentioning
confidence: 99%
“…The authors continued their work in this direction and recently published data on an improved 3D model of HNSCC, in which the cellular component was represented by two types of cells-UM-SCC-38 and A8-HVFFs (immortalized human vocal fold fibroblasts) in a ratio of 1:2. In the process of culturing the model, spheroid development and growth over time with cancer cells in the core and fibroblasts in the periphery were observed [104].…”
Section: Bioprinted Modelsmentioning
confidence: 99%
“…It can be concluded that the 3D bioprinted model of HNSCC is essentially an improved tissue-engineered model, where a hydrogel is used as a scaffold, and the use of a printing method instead of the usual layering of the gel on a substrate allows for more accurate control of the compliance of the tissue architecture with the specified parameters. So far, bioprinted HNSCC models have been obtained only for immortalized lines, which is due to the need to use a large number of cells to obtain the desired result (in [104] cells were encapsulated in gel at a final concentration of 10 million cells per ml). Obviously, an important task for researchers is to obtain such 3D models with HNSCC patient-derived cells to closely match more biological features and potentially use this technique for personalized medicine.…”
Section: Bioprinted Modelsmentioning
confidence: 99%